Effect of Extraction Temperature of Molecularly Imprinted Polymer in Chloramphenicol Adsorption using UV-Vis Spectrophotometry Based on Diazotation Reaction - Oktaningtias, Eka Faradila; Sianita, Maria Monica (Jurnal Pijar Mipa, 2025)
Chloramphenicol is an antibiotic commonly used in aquaculture. The overuse of antibiotics poses a danger. CAP will precipitate, and the residue will accumulate in the human body, threatening human health. Efforts are made to make media to overcome the CAP problem, one of which is the manufacture of molecularly imprinted polymers. The characteristic of this polymer is a mould or template that is reacted during synthesis and then withdrawn in the extraction process to form a selective mould. One factor that affects extraction is temperature. This study aimed to determine the effect of extraction temperature on chloramphenicol adsorption. The polymerisation was carried out using the precipitation polymerization method, and extraction was done using the batch method. The test used diazotation-based Uv-Vis spectrophotometry. The temperatures used were 60,70 and 80℃, which resulted in extraction percentages of 75.64%, 89.63% and 74.08%, respectively. For the adsorption process, the concentration variation for each MIP was 10, 25, 50, 75 and 100 ppm. Higher concentrations resulted in more adsorption, but the 100 ppm concentration decreased. The test showed that temperature affected the extraction and CAP adsorption results. Polymer characterisation was carried out with FTIR Polymer NIP results showing the presence of NO2 groups characteristic of CAP found at wave numbers 1536 cm-1 and 1322 cm-1. In MIP, there is an Imprinting Factor (IF). The IF value obtained is more than 1, so it can be said that the moulding results are good.